Slime molds (Myxomycetes) causing a “disease” in crop plants and cultivated mushrooms - Zhang, Zhaojuan; Zhai, Chao; Li, Yu; Stephenson, Steven L.; Liu, Pu (Frontiers in Plant Science, 2024)
Myxomycetes (plasmodial slime molds) are eukaryotic protist predators that are associated with wood, leaf litter, and soil in forests, where they feed on bacteria, protozoans, and (to a more limited extent) fungi. The health of crop plants is essential because they represent a primary food source for humans. However, when myxomycetes produce numerous fruiting bodies on the stems and leaves of crop plants, which is herein referred to as a myxomycete colonization, this has the potential of interfering with plant photosynthesis, transpiration and respiration by blocking out light and covering stomata. Myxomycetes are not pathogens, but their occurrence on plants can be mistakenly interpreted as some type of infection. However, this phenomenon has been largely ignored. This paper provides a comprehensive overview of the taxonomic and economic diversity of the organisms involved in myxomycete colonization.In addition, the various types of myxomycete colonization reported in the literature are described and discussed, a number of images provided, and cultural and chemical prevention and control measures are summarized. The latter should be of significant relevance for local production of crops and plant protective stations. While myxomycetes are not pathogens of crop plants, some species can seriously impact commercially grown mushrooms. Reports of myxomycetes affecting mushrooms are also described in this paper.